The Role of Marketing Strategies for Improving Retail Coverage in West Bandung - Melinda Kwan; Wauzi Alfian (Journal of Social Growth and Development Studies, 2025)
Retail coverage refers to the distribution range of retail products to various outlets or stores within a specific geographical area according to the determined target market. Retail coverage is a crucial aspect for companies to ensure their products are available in numerous stores and easily accessible to consumers. The objective of this research is to explain the role of marketing strategies in improving retail coverage in the West Bandung area. The impact of marketing strategies on retail coverage is evident through significant increases in the number of stores and sales. The research object is PT. Borwita Citra Prima's Bandung branch, specifically focusing on the West Bandung region. This study employs a qualitative descriptive research method with a case study approach. Data collection techniques employed in this research include observation, interviews, and documentation, while data analysis methods involve data reduction, data registration, conclusion drawing, and final verification of research validity through credibility tests. The results of this study demonstrate a significant impact on PT. Borwita Citra Prima's Bandung branch, particularly in the West Bandung area. This strategy can be implemented in other regions to improve retail coverage and reduce business burdens on wholesale stores.